2023
DOI: 10.1007/s10526-023-10185-7
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of white grubs from forestry and sugarcane plantations in South Africa to entomopathogenic nematodes

Abstract: The control of white grub (Coleoptera: Scarabaeidae) pests of sugarcane and forest plantations is difficult due to their cryptic nature and resistance to chemicals. This study evaluated the potential use of entomopathogenic nematodes (EPNs) as an alternative control method. Laboratory bioassays were performed with 12 locally isolated EPN species to determine the susceptibility of third instar larvae of the white grubs Schizonycha affinis Boheman, Pegylis sommeri Burmeister, Monochelus sp. and Maladera sp. 4. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…In terms of the pathogenicity of the isolated nematodes on third instar larvae of white grubs, Katumanyane et al . (2023) showed that Steinernema fabii provided 63 % mortality of Maladera sp. 4 in soil bioassays.…”
Section: Resultsmentioning
confidence: 99%
“…In terms of the pathogenicity of the isolated nematodes on third instar larvae of white grubs, Katumanyane et al . (2023) showed that Steinernema fabii provided 63 % mortality of Maladera sp. 4 in soil bioassays.…”
Section: Resultsmentioning
confidence: 99%
“…While R. regina is a natural entomopathogen of P. polyphylla, it remains uncertain whether this specificity extends to other white grubs [65]. White grubs exhibit a diverse array of behavioral, morphological, physiological, and immunological defenses, suggesting the possibility of different host preferences [66,67]. Therefore, future research should explore how these attributes influence the foraging behavior of nematodes.…”
Section: Plos Onementioning
confidence: 99%
“…A lot of work has been done in South Africa, mostly under laboratory environment, Vernon et al (2021), conducted a study in controlling false codling moth (FCM), Thaumatotibia leucotreta (Meyrick) (Lepidoptera: Tortricidae) using several entomopathogenic nematode (EPNs) and entomopathogenic fungus (EPFs) species, that were identified from soil samples collected from orchards and vineyards throughout the Western Cape province in South Africa. Katumanyane et al (2023), also conducted a study in "Susceptibility of white grubs from forestry and sugarcane plantations in South Africa to entomopathogenic nematodes". He concluded that; the dissection of insect cadavers revealed possible limiting factors for low susceptibility, due to the nematodes and their associated symbiotic bacteria's inability to infect the insect haemocoel, with no EPNs being found inside some of the cadavers.…”
Section: Latest Developments In Epn Research and Product Development Samentioning
confidence: 99%